Building Sharia Bank Customer Loyalty Through a Religious Value-Based Approach and Service Satisfaction - Hakim, Ulil Akbar; Jaharuddin, Jaharuddin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to analyze the impact of service quality, customer satisfaction, and trust on customer loyalty, considering religiosity as a moderating variable. The research was conducted on Islamic bank customers in Indonesia using a quantitative approach based on the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. Data were collected from 126 respondents, with 102 meeting the research criteria. The results indicate that customer satisfaction has the most significant influence on customer loyalty, while service quality and trust also positively contribute to loyalty, albeit to a lesser extent. Additionally, service quality and satisfaction significantly enhance customer religiosity, whereas trust does not show a significant effect on religiosity. Religiosity, while not directly affecting loyalty, serves as a moderating variable that strengthens the relationship between service quality and satisfaction with loyalty. The implications of this study emphasize the importance of enhancing customer experience through high-quality services aligned with Sharia principles, as well as fostering satisfaction and trust to build long-term loyalty. These findings provide practical insights for Islamic bank management to design strategies based on religious values to strengthen customer relationships. Furthermore, this study offers theoretical insights into the critical role of religiosity as a moderating factor in fostering customer loyalty in the Islamic banking sector.